Needs Assessment and Training Methodologies for Medical Practitioners towards Emerging Digital Technology - M.Savitha; Dr S. Praveen Kumar (The Bioscan, 2025)
Technological adoption in healthcare sector is critical in enhancing operational efficiency, improving patient outcomes and accelerating clinical research. In this case, it is important that medical practitioners have become skilled in the use of skills and tools for making appropriate decisions in the fast-paced environment that shifting in this case. This abstract examines the various training methods aimed at equipping medical staff with the ability to apply and comprehend digital technologies. Such methods involve the use of digital learning environments, simulation, and hands-on training as well as other mixed approaches whereby video technology is combined with conventional teaching that involves face to face content delivery. At the same time, talks and joint learning environments help to foster their exchanges and solving concrete tasks. This way, the realism of training opportunities is often the focus to make sure that medical professionals are able to work with these tools. Technologies including digital imaging technologies, telemedicine, electronic health records (EHR), and artificial intelligence (AI) in diagnoses are technologies that medical practitioners have to familiarize themselves with. Also addressed are range of training approaches that though can improve their technical capabilities, also concern the ethical, privacy, and security issues related to this.